Excel english early skills book 7: learning the alphabet - Calder, Hunter (Oxford University Press Karachi, 2006)
"Excel English Early Skills Book 7: Learning the Alphabet" helps young children familiarize themselves with the letters of the alphabet through engaging activities and colorful illustrations. The book focuses on letter recognition, sound associations, and foundational writing skills to support early literacy development.